The effect of economic conditions, sanctions and modernization of administrative systems on motor vehicle taxpayer compliance at samsat south Medan - Dapot Lumban Gaol; Agus Purwoko; Erika Revida (Jurnal Ekonomi, 2024)
Taxpayer compliance is one of the measuring instruments for the success of motor vehicle tax revenues. This study aims to analyze the influence of economic conditions, tax sanctions and modernization of the tax administration system towards the compliance of motor vehicle taxpayers in Medan Selatan Samsat. The theory used in this study is Risk Opposing Theory (Risk Aversion Theory). The population in this study was all motor vehicle taxpayers registered at the Joint Office in Medan Selatan Samsat with a total of 271 samples. The sample determination technique is accidental sampling. This research is a type of quantitative research using primary data, data obtained by spreading questionnaires. The analysis technique used in this study is logistic regression by assessing the overall model (Overall Model Fit), the feasibility of the regression model (Goodness of Fit Test), Logistic Regression and Wald Test. The results showed that economic conditions and modernization of administrative systems had no significant effect on taxpayer compliance while sanctions had a significant effect on motor vehicle taxpayer compliance at Medan Selatan Samsat.